Immunopathogenetic Disorders in Patients with Herpesvirus Infections - Z. A. Kambachokova; M. A. Khamurzova; R. M. Aramisova; L. M. Timmoeva; Zh. L. Shogenova; A. G. Shokueva; T. B. Kipkeeva; M. Kh. Dadaev (Антибиотики и Химиотерапия, 2020)
Immunological disorders were studied in 68 patients with herpesvirus infections (41 women and 27 men) aged 18 to 55 years. All patients were examined clinically, also laboratory tests were conducted during the period of exacerbation and clinical remission. Patients with herpesvirus infections showed a significant decrease in the relative number of CD3+, CD4+ T-lymphocytes and their subpopulations during exacerbation of herpes infection. A decrease in the content of CD 3+, CD4+ T-cells during exacerbation of the disease was associated with an increase in CD8+ T-lymphocytes. The immunoregulatory index also decreased. The relative number of CD19+ B cells significantly increased in the exacerbation stage. During the period of remission, the number of CD19+ lymphocytes decreased, remaining above the normal range in patients with severe disease. Studies have shown that patients with herpesvirus infections have immunopathological disorders both during the relapse period and during the remission period, which must be taken into account when treating these patients.